The Effect of Quality of Work Life and Work Environment on Employee Performance at PT Wijaya Karya Rekayasa Konstruksi East Jakarta - Rima Handayani; Eni Puji Astuti; Rahmi Hermawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine whether there is an influence on the quality of work life and work environment on employee performance at PT Wijaya Karya Rekayasa Konstruksi East Jakarta. This research method uses quantitative methods with a descriptive approach. The sampling technique is saturated with all the population as samples, namely as many as 130 respondents. The data collection method used is the observation method by distributing questionnaires. The data analysis used is validity test, reliability test, correlation test, simple linear regression test, multiple linear regression test, determination test, classical assumption test, hypothesis test (t test), and hypothesis test (F test). Based on the research results, + 0.509. The correlation coefficient value is 0.622, meaning that the independent variable has a strong relationship with the dependent variable. The coefficient of determination shows that the variable quality of work life and work environment contributes 38.6% to employee performance, while the remaining 61.4% is influenced by other factors not examined. The results of the t-test that the coefficient value for the Quality of Work Life variable is 0.226 with tcount of 3,079 > ttable 1,979 the tcount value of Quality of Work Life is greater than the value of ttable and the significant level of t is less than 0.05 (0.03 <0.05) then H1 is accepted, while for the work environment variable is 0.509 with tcount 7.424 > ttable 1.979 and the significant level t is less than 0.05 (0.00 <0.05) then H1 is accepted.